Biosystems Engineering of Prokaryotes with Tumor-Killing Capacities - Kalyoncu, Ebuzer; T. Olmez, Tolga; D. Ozkan, Alper; F. Sarioglu, Omer (Current Pharmaceutical Design, 2016)
Certain bacteria selectively attack tumor tissues and trigger tumor shrinkage by producing toxins and modulating the local immune system, but their clinical utility is limited because of the dangers posed by systemic infection. Genetic engineering can be used to minimize the risks associated with tumor-targeting pathogens, as well as to increase their efficiency in killing tumor cells. Advances in genetic circuit design have led to the development of bacterial strains with enhanced tumor-targeting capacities and the ability to secrete therapeutics, cytotoxic proteins and prodrug-cleaving enzymes, which allows their safe and effective use for cancer treatment. The present review details the recent advances in the design and application of these modified bacterial strains.
Keywords: Synthetic biology